Comparison of Bispectral Index Monitoring With the Critical-Care Pain Observation Tool in the Pain Assessment of Intubated Adult Patients After Cardiac Surgery - Faritous, Zahra (Anesth Pain Med, 2016)
BACKGROUND: Detecting pain is crucial in sedated and mechanically ventilated patients, as they are unable to communicate verbally. OBJECTIVES: This study aimed to compare Bispectral index (BIS) monitoring with the Critical-care pain observation tool (CPOT) and vital signs for pain assessment during painful procedures in intubated adult patients after cardiac surgery. MATERIALS AND METHODS: Seventy consecutive patients who underwent cardiac surgery (coronary artery bypass graft or valvular surgery) were enrolled in the study. Pain evaluations were performed early after the operation in the intubated and sedated patients by using BIS and CPOT, and also checking the vital signs. The pain assessments were done at three different times: 1) baseline (immediately before any painful procedure, including tracheal suctioning or changing the patient’s position), 2) during any painful procedure, and 3) five minutes after the procedure (recovery time). RESULTS: The mean values for CPOT, BIS, and mean arterial pressure (MAP) scores were significantly different at different times; they were increased during suctioning or changing position, and decreased five minutes after these procedures (CPOT: 3.98 ± 1.65 versus 1.31 ± 1.07, respectively (P ≤ 0.0001); BIS: 84.94 ± 10.52 versus 63.48 ± 12.17, respectively (P ≤ 0.0001); MAP: 92.88 ± 15.37 versus 89.77 ± 14.72, respectively (P = 0.003)). Change in heart rate (HR) was not significant over time (95.68 ± 16.78 versus 93.61 ± 16.56, respectively; P = 0.34). CPOT scores were significantly positively correlated with BIS at baseline, during painful stimulation, and at recovery time, but were not correlated with HR or MAP, except at baseline. BIS scores were significantly correlated with MAP but not with HR. CONCLUSIONS: It appears that BIS monitoring can be used for pain assessment along with the CPOT tool in intubated patients, and it is much more sensitive than monitoring of hemodynamic changes. BIS monitoring can be used more efficiently in intubated patients under deep sedation in the ICU.